Determination of macroeconomic factors on Indonesia's oil and gas imports: an ECM approach - Hasibuan, Sri Rahayu; Mahardika, Mayza Hanif Abbad; Addaruqutni, Adnan Dahiya; Kartiasih, Fitri (Nur Science Institute, 2025)
The oil and gas trade deficit can negatively impact Indonesia’s economy in the long term, highlighting the need to identify key factors influencing oil and gas imports. This study analyzes the effects of inflation, exchange rates, and foreign exchange reserves on oil and gas imports using the Error Correction Model (ECM), which captures both short-term and long-term dynamics. Monthly data from January 2003 to December 2023 were used, with a natural logarithm transformation applied to address non-stationarity. The results show that, in the long term, inflation and foreign exchange reserves significantly and positively affect oil and gas imports, while the exchange rate has a significant negative effect. In the short term, these variables show no significant impact except for the error correction term (ECT), which is negative and significant—indicating a gradual adjustment toward long-term equilibrium. The findings support policy efforts focused on maintaining price stability, exchange rate management, and adequate foreign exchange reserves to ensure a more sustainable oil and gas trade balance.